Relationships among bacterial cell size, diversity, and taxonomy in rumen - Liu, Sijia; Zheng, Nan; Wang, Jiaqi; Zhao, Shengguo (Frontiers in Microbiology, 2024)
Introduction The rumen microbial community plays a crucial role in the digestion and metabolic processes of ruminants. Although sequencing-based studies have helped reveal the diversity and functions of bacteria in the rumen, their physiological and biochemical characteristics, as well as their dynamic regulation along the digestion process in the rumen, remain poorly understood. Addressing these gaps requires pure culture studies to demystify the intricate mechanisms at play. Bacteria exhibit morphological differentiation associated with different species. Based on the difference in size or shape of microorganisms, size fractionation by filters with various pore sizes can be used to separate them. Methods In this study, we used polyvinylidene difluoride filters with pore sizes of 300, 120, 80, 40, 20, 8, 6, 2.1, and 0.6 μm. Bacterial suspensions were successively passed through these filters for the analysis of microbial population distribution using 16S rRNA gene sequences. Results We found that bacteria from the different pore sizes were clustered into four branches (> 120 μm, 40–120 μm, 6–20 μm, 20–40 μm, and < 0.6 μm), indicating that size fractionation had effects on enriching specific groups but could not effectively separate dominant groups by cell size alone. The species of unclassified Flavobacterium, unclassified Chryseobacterium, unclassified Delftia, Methylotenera mobilis, unclassified Caulobacteraceae, unclassified Oligella, unclassified Sphingomonas, unclassified Stenotrophomonas, unclassified Shuttleworthia, unclassified Sutterella, unclassified Alphaproteobacteria, and unclassified SR1 can be efficiently enriched or separated by size fractionation. Discussion In this study, we investigated the diversity of sorted bacteria populations in the rumen for preliminary investigations of the relationship between the size and classification of rumen bacteria that have the potential to improve our ability to isolate and culture bacteria from the rumen in the future.